Efektivitas high-intensity interval training terhadap kontrol glikemik (HbA1c) dan sensitivitas insulin pada pasien diabetes melitus tipe 2: A systematic literature review - Muhammad Raihan; Aurora Fervita; Muhammad Dihya Aby Abdi Manaf (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease characterized by hyperglycemia due to insulin resistance and impaired insulin secretion, necessitating effective interventions to improve glycemic control and insulin sensitivity. One widely studied non-pharmacological approach is high-intensity interval training (HIIT). Purpose: To analyze the effectiveness of HIIT on glycemic control as measured by HbA1c and insulin sensitivity in patients with T2DM. Method: This was a systematic literature review based on the PRISMA guidelines. A literature search was conducted in PubMed, Scopus, and Google Scholar for articles published between 2020 and 2025, yielding 25 studies that met the inclusion criteria. Results: HIIT generally lowers HbA1c and fasting blood glucose, as well as improves HOMA-IR, fasting insulin, and glucose disposal rate. However, the magnitude of the effect varies across studies and is not always superior to moderate-intensity continuous training (MICT), particularly in isoenergetic designs or long-term interventions. Conclusion: Overall, HIIT can be viewed as an effective and efficient exercise strategy worthy of consideration in the management of T2DM, especially when designed with an appropriate protocol and performed consistently. Keywords: Glycemic Control; HbA1c; High-Intensity Interval Training; Insulin Sensitivity; Type 2 Diabetes Mellitus.